The interplay of competition and cooperation - Hoffmann, Werner; Lavie, Dovev; Reuer, Jeffrey J.; Shipilov, Andrew (Strategic Management Journal, 2018)
[Research streams on competition and cooperation are central to the field of strategic management but have evolved independently. The emerging literature on coopetition has brought attention to the phenomenon of simultaneous competition and cooperation, yet the interplay between the two has remained under-researched. We offer a roadmap for studying this interplay, which identifies some of its antecedents and consequences, highlights debates concerning the nature of competition and cooperation and the association between the two, and directs attention to the tension between competition and cooperation and the alternative approaches for managing this tension. We discuss the broader implications of the interplay, note some intriguing open questions, offer directions for future research, and present an organizing framework for the interplay of competition and cooperation.]